MOBILE APPLICATIONS AS AN EFFECTIVE TOOL IN PHYSICS EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the ways and prospects of using mobile applications in teaching physics.